Transvestites in educational contexts: tensions and resistances experienced by transvestites in the City of Natal, Brazil (Revista Contexto & Educação, 2024)
This article aims to problematize the challenges faced by transvestites in the schooling process in basic and higher education institutions in the city of Natal, Brazil. Based on a cartographic process, the researchers problematize the experiences of transvestites in the light of queer theory and illustrate the schooling paths marked by processes of tension and resistance. The study reveals the relationships of transvestites with other actors in educational contexts from the perspective of transvestiteness, understood as the multiple forms of transvestite expression, and defends a school based on the education of difference. It is concluded that, despite advances in legislation and in the field of research on the subject, the stigmatization and violation of the multiple forms of expression of transvestite life in the school context remains explicit.
Keywords: transvestites; education; LGBTQIA; transvestites at school